A non-invasive identification of hormone metabolites, gonadal event and reproductive status of captive female tigers - HERI DWI PUTRANTO (Society for Indonesian Biodiversity, 2011)
Putranto HD (2011) A non-invasive identification of hormone metabolites, gonadal event and reproductive status of captive female tigers. Biodiversitas 12: 131-135. As a non-invasive method, fecal sample provides some advantage for animal and collector. The purpose of the present study were to monitor the reproductive status of female Siberian tigers (Panthera tigris altaica) by assessing changes in fecal during natural ovarian activity and pregnancy and to identify whether progesterone (P4) exists and what kinds of P4 metabolites excreted into the feces. Two female tigers were fed a diet consisting of meat. Drinking water was available ad libitum. Feces were collected ones to twice a week. The fecal contents of P4 and estradiol-17Î² (E2) were determined by EIA and P4 metabolites were separated by a modified HPLC. The EIA results shown that during its natural ovarian activity the E2 contents showed cyclic changes at the average of 27.0 d interval, however, no distinct cycles were shown in fecal P4 contents of non-pregnant tiger. In contrary, the fecal P4 contents in pregnant tiger increased remarkably after copulation approximately 2- to 6-fold higher than the mean value. The HPLC results indicated that two peaks were primarily detected fraction 63- 64 min (identified metabolites) and fraction 85 min (not identified metabolite) in feces of pregnant tiger. However, P4 detected only small amount in feces. It is possible to assess non-invasively gonadalevents such as luteal or follicular activity or ovulation of Siberian tigers by endocrine monitoring based on fecal P4 and E2 to understand reproductive status.